Contributions of the immunogold technique to investigation of the biology of peroxisomes - Fahimi, H. Dariush; Reich, Daniel; Völkl, Alfred; Baumgart-Vogt, Eveline (Histochemistry and cell biology, 1996)
The immunogold labeling technique has been extremely useful in investigation of the structure and function of peroxisomes. In this report a few examples of the application of this technique with significant implications in the field are briefly reviewd. The problem of extra-peroxisomal catalase, the subject of long controversy between the biochemists and cytochemists, was settled with the immunogold technique, which unequivocally revealed the presence of that enzyme not only in the cytoplasm, but also in the euchromatin region of nucleus, in addition to peroxisomes. On the other hand, lactate dehydrogenase, a typical cytoplasmic protein, has also been shown recently to be present in peroxisomes and to be involved in the reoxidation of NADH produced by the peroxisomal β-oxidation system. The immunogold technique has revealed several distinct compartments in the matrix of mammalian peroxisomes: urate oxidase in the crystalline cores, α-hydroxy acid oxidase B in the marginal plates andd-amino acid oxidase in a non-crystaline condensed region of matrix. The specific alterations of peroxisomal proteins are reflected in their immunolabeling density with gold particles. Quantitation of gold-label by automatic image analysis has revealed that the induction of lipid β-oxidation enzyme proteins by diverse hypolipidemic drugs is initiated and more pronounced in the pericentral region of the liver lobule. Finally, immunogold labeling with an antibody to 70 kDa peroxisomal membrane protein has identified a novel class of small peroxisomes that initially incorporate radioactive amino acids more efficiently than regular peroxisomes and thus may represent early stages in the biogenesis of peroxisomes.